2021
DOI: 10.3389/fmolb.2021.706122
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of SARS-Cov-2 Propagation Versus ACE2 Fits COVID-19 Lethality Across Age and Sex and Predicts That of SARS

Abstract: The fatality rate of Covid-19 escalates with age and is larger in men than women. I show that these variations correlate strongly with the level of the viral receptor protein ACE2 in rat lungs, which is consistent with the still limited data on human ACE2. Surprisingly, lower receptor levels correlate with higher fatality. I propose two possible explanations of this negative correlation: First, a previous mathematical model predicts that the velocity of viral progression in the organism as a function of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 87 publications
3
16
0
Order By: Relevance
“…As ACE2 expression is a key factor for SARS-CoV-2 entry into host cells, it is reasonable to assume that low levels of ACE2 would protect against infection, viral amplification, and ultimately a lethal outcome in COVID-19. However, according to a recent model of viral dynamics and gene expression of ACE2 in rats and humans, there is a strong negative correlation between ACE2 and lethality [120]. This hypothesis agrees with research demonstrating that the ACE2 receptor is expressed at lower levels in men than in women, and decreases with age, inflammatory-related comorbidity, and with reduced testosterone and estrogen levels [121].…”
Section: Effects Of Physical Activity and Exercise On Human Biology In View Of Covid-19supporting
confidence: 80%
“…As ACE2 expression is a key factor for SARS-CoV-2 entry into host cells, it is reasonable to assume that low levels of ACE2 would protect against infection, viral amplification, and ultimately a lethal outcome in COVID-19. However, according to a recent model of viral dynamics and gene expression of ACE2 in rats and humans, there is a strong negative correlation between ACE2 and lethality [120]. This hypothesis agrees with research demonstrating that the ACE2 receptor is expressed at lower levels in men than in women, and decreases with age, inflammatory-related comorbidity, and with reduced testosterone and estrogen levels [121].…”
Section: Effects Of Physical Activity and Exercise On Human Biology In View Of Covid-19supporting
confidence: 80%
“…Mathematical models of virus propagation, tested with experiments with bacteriophages, suggest that there is an optimal receptor density at which the virus propagates fastest, with viral velocity declining both for lower and for higher receptor density (Ortega-Cejas et al, 2004) (see Figure 5). A mathematical model of the dependence of Covid-19 mortality on receptor density fitted to both Covid-19 and SARS 2003 data of lethality across age and sex suggests that both viruses propagate in a regime in which increasing receptor density slows down their propagation (Bastolla, 2021). Thus, the inverse relation between ACE2 expression and Covid-19 severity is not implausible.…”
Section: Effect Of Receptor Level On Viral Propagationmentioning
confidence: 97%
“…As discussed in more detail in Ref. (Bastolla, 2021), this inverse relationship between ACE2 levels and Covid-19 severity might rationalize not only the influence of age and sex but also most of the other known risk factors of Covid-19 examined in the OpenSAFELY study (Williamson et al, 2020), including diabetes, hypertension, obesity, vitamin D deficit (that may explain at least part of the risk factors connected with ethnicity) and perhaps even the curious protecting effect of smoke that increases ACE2 expression (Saheb Sharif-Askari et al, 2020).…”
Section: Comorbidities Support a Negative Relation Between Angiotensi...mentioning
confidence: 99%
“…Moreover, despite the high transmissibility of SARS-CoV-2, there are highly exposed people who have not acquired the infection. Genetic factors along with other risk factors can determine the susceptibility of each individual to infection, but those are largely unknown ( 13 , 14 ). The goal of our study is to provide some insight into why health care worker (HCW) with reported high-risk exposures to virus and persons cohabiting without protection with infected relatives remained uninfected despite constant contact with the virus.…”
Section: Introductionmentioning
confidence: 99%